Surgical Management of Sertoli Cell Tumour in Dogs: Report of two Cases - Padaliya, Nilesh R.; Vadalia, Jignesh V.; Talekar, Shivaji H.; Bhatt, Raghuvir H.; Bhadaniya , Amit. R.; Kalaria, Vinay A. (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Two non-descript male dogs were presented with history of sizable swelling in inguinal region which was gradually increased within a period of three months. Clinical examinations revealed difficulty to walk and presence of fluctuating, painful, hard mass in the scrotum. Under general anaesthesia using ketamine-diazepam induction and isoflurane maintenance, the mass was resected after giving direct incision over it and transfixing the vasculatures followed by routine wound closure. Postoperatively, antibiotic and analgesic drugs were given along with local dressing for five days. Both animals recovered uneventfully without any post-operative complications. Histopathological investigation confirmed presence of sertoli cell tumour in both cases.
Keywords: Male dog; Sertoli cell tumour; Surgical intervention; Testes